2013
DOI: 10.1111/jch.12095
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of True Therapeutic Inertia in Blood Pressure Control in an Academic Chronic Kidney Disease Clinic

Abstract: Therapeutic inertia (TI) in blood pressure (BP) control has been traditionally defined as failure to initiate or intensify therapy when treatment goals are not met. The fallacy with this definition is that TI may be overestimated because it includes hypertensive patients deliberately uncontrolled. This is a retrospective chart review study that evaluated physicians' response to an uncontrolled clinic BP reading in a population of patients with stage 3 to 5 chronic kidney disease (CKD) and hypertension. Of 429 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Overall, therapeutic inertia occurred in one-third of patients of our cohort; a similar frequency has been detected for erythropoiesis stimulating agents (ESA) treatment and antihypertensive drugs in renal clinics [4,17]. This phenomenon was more frequent for the treatment of hyperphosphatemia (Fig.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Overall, therapeutic inertia occurred in one-third of patients of our cohort; a similar frequency has been detected for erythropoiesis stimulating agents (ESA) treatment and antihypertensive drugs in renal clinics [4,17]. This phenomenon was more frequent for the treatment of hyperphosphatemia (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…This is particularly important for physicians when findings derived from selected cohorts of randomized clinical trials are applied to an unselected CKD population requiring individualized strategies which must take into account the interaction between the single out-oftarget factor and the whole spectrum of the patient's comorbidities [13]. Second, knowledge about the use of MBD medications makes it possible to identify opportunities for improving care by limiting therapeutic inertia, a phenomenon described in the nephrology setting in relation to hypertension, anemia and lipid management [4,17,18]. Finally, identification of CKD-MBD treatment patterns in nationally representative outpatient nephrology settings may also help to design evidence-based algorithms by identifying the variations in physician prescriptions for ND-CKD and the reasons for such variations.…”
Section: Introductionmentioning
confidence: 99%
“…In a national, multicenter, observational, and cross-sectional study in primary care and specialist (hospital) physicians, therapeutic inertia occurred in 75% of the consultations in which treatment change was indicated [16]. In a study performed in an academic chronic kidney disease, therapeutic inertia was found in 44% of patients [33].…”
Section: Discussionmentioning
confidence: 98%
“…One of these is physician adherence to the prescribing recommendations in whichever guideline(s) they choose to read. Physician adherence is far from optimal in numerous geographic regions, and therapeutic inertia is widely discussed in the literature . Another is patient adherence to prescribed treatment regimens .…”
Section: Treatment‐resistant Hypertensionmentioning
confidence: 99%